2013
DOI: 10.1186/2044-5040-3-27
|View full text |Cite
|
Sign up to set email alerts
|

Rb1 loss modifies but does not initiate alveolar rhabdomyosarcoma

Abstract: BackgroundAlveolar rhabdomyosarcoma (aRMS) is a myogenic childhood sarcoma frequently associated with a translocation-mediated fusion gene, Pax3:Foxo1a.MethodsWe investigated the complementary role of Rb1 loss in aRMS tumor initiation and progression using conditional mouse models.ResultsRb1 loss was not a necessary and sufficient mutational event for rhabdomyosarcomagenesis, nor a strong cooperative initiating mutation. Instead, Rb1 loss was a modifier of progression and increased anaplasia and pleomorphism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Recent work has shown that the loss of RB1 does not appear to initiate RMS, but is a disease modifier. The loss of RB1 in an ERMS or an ARMS model modifies the tumour phenotype to mimic an undifferentiated pleomorphic sarcoma ( Rubin et al , 2011 ) or a pleomorphic RMS identity ( Kikuchi et al , 2013 ), respectively. The interplay between pRB and TBX2 in RMS or normal skeletal muscle is unknown.…”
Section: Oncogenic Role and Potential Regulation Of Tbx2 In Rmsmentioning
confidence: 99%
“…Recent work has shown that the loss of RB1 does not appear to initiate RMS, but is a disease modifier. The loss of RB1 in an ERMS or an ARMS model modifies the tumour phenotype to mimic an undifferentiated pleomorphic sarcoma ( Rubin et al , 2011 ) or a pleomorphic RMS identity ( Kikuchi et al , 2013 ), respectively. The interplay between pRB and TBX2 in RMS or normal skeletal muscle is unknown.…”
Section: Oncogenic Role and Potential Regulation Of Tbx2 In Rmsmentioning
confidence: 99%
“…Similarly, alterations in RB1 pathways and in genes encoding proteins that regulate RB1 function such as CDK4 (amplification) and CDKN2A and CDKN2B (deletions) have been identified in ARMS [Kohashi et al, 2008;Kikuchi et al, 2013;Shern et al, 2014]. Our case demonstrated a genomic loss at chromosome 13q14.11q14.3 containing the RB1 locus that is situated close to the amplified FOXO1 region ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Four samples of formalin-xed para n embedded (FFPE) human RMS were available to include in a custom mouse model tissue microarray (TMA) (1 x aRMS, 3 x eRMS). Forty-eight murine model sarcomas were also included, representing developmental stages and genotypes including early myoblast (origin), postnatal stem cell (origin), maturing myo ber (origin), Pax3:Foxo1-expressing, Trp53 wild type or mutated and Rb1wildtype or mutated (5,7,10).…”
Section: Tissue Microarraysmentioning
confidence: 99%
“…Lymphatic and hematogenous (pulmonary) metastasis is a predominant feature(4)and a primary cause of mortality in these models (8). We characterized these soft tissue sarcoma models and demonstrate them to be representative of the human diseases by histopathology, gene expression and other features (3,4,9,10). Furthermore, these conditional models have the special features of knowing the cell-of-origin as well as the mutational pro le making them a valuable tool to study RMS ( Figure 1).…”
Section: Introductionmentioning
confidence: 97%